PERAN MEDIASI DALAM PENYELESAIAN SENGKETA PELAYANAN KESEHATAN: KAJIAN RESTORATIF - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2025)
The role of mediation in resolving healthcare disputes has become increasingly relevant amid rising conflicts involving patients and healthcare providers. This study highlights the importance of a restorative approach in mediation, which focuses not only on conflict resolution but also on improving relationships, restoring trust, and fulfilling the emotional and material needs of the parties involved. This approach offers a more humane, efficient, and empathetic alternative to conventional litigation, emphasising open dialogue and mutually beneficial outcomes. Through restorative-based mediation, healthcare systems can create responsive and empowering dispute resolution mechanisms, while strengthening the dimensions of social justice and human values in the healthcare sector.